LIVING HARMONI: Praktik Moderasi Beragama di Desa Toabo, Sulawesi Barat - Tahir, Bakri; Heriamsal, Krisman (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
Indonesia's diversity frequently faces challenges related to potential conflicts stemming from ethnic, religious, racial, and intergroup differences (SARA). Amidst increasing incidents of intolerance, Toabo Village in Mamuju Regency, West Sulawesi, emerges as a success story of how a local community sustains social harmony through the implementation of religious moderation. This study aims to explore the factors contributing to Toabo’s success and sustainability as a Village of Religious Moderation. Employing a qualitative analytical approach with a case study design, data were collected through literature review and in-depth interviews with community members, religious leaders, and local government officials. The findings reveal several key factors underpinning this success: the availability of worship facilities for all religious groups, interfaith participation in social and religious activities, the active role of religious leaders and village authorities in fostering harmony, equitable power distribution, and the integration of religious moderation values into the local education curriculum. These findings highlight the importance of community-based approaches in promoting peaceful and inclusive coexistence.